Man-eaters (2018), volume 1 ebook - Cain, Chelsea (Man-Eaters (2018), 2019)
Adolescent girls can be real monsters. Maude is twelve which is just about that age when some girls turn into flesh-eating wildcats. As her detective dad investigates a series of strange mauling attacks, Maude begins to worry that she might be the killer. From the creative team that brought you the groundbreaking Eisner-nominated series Mockingbird, this trade paperback collects the first story arc of the unconventional coming-of-age taleincluding the informative survival handbook,  "CAT FIGHT! A BOYS" GUIDE TO DANGEROUS CATS" and all-new never-before-published extras! Collects MAN-EATERS #1-4. Author: Chelsea Cain. Illustrator: Kate Niemczyk . 2019 Ministry of Trouble, Inc..